1987
DOI: 10.1203/00006450-198704000-00007
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Hypotension on Brain Energy State during Prolonged Neonatal Seizure

Abstract: Clinical and experimental evidence show that systemic hypotension may occur during the course of prolonged seizure (1-3). Nonetheless, the physiologic and metabolic consequences of hypotension on the outcome of neonatal seizure is unclear (4). Because metabolic demands on the brain increase greatly during seizure, it is hypothesized that even a modest reduction in CBF produces relative ischemia and further tissue damage.Autoregulation of CBF ordinarily maintains cerebral perfusion during systemic hypotension (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

1988
1988
2025
2025

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 7 publications
0
2
0
1
Order By: Relevance
“…Changes in brain energy stores were not affected by glucose availability, although differences in alanine, glycine, and P-hydroxybutyrate were found in the 'H extracts. Hypotension had little effect on the 31P changes (Cowan et al, 1987).…”
Section: Addition Of 'H Mrsmentioning
confidence: 78%
See 1 more Smart Citation
“…Changes in brain energy stores were not affected by glucose availability, although differences in alanine, glycine, and P-hydroxybutyrate were found in the 'H extracts. Hypotension had little effect on the 31P changes (Cowan et al, 1987).…”
Section: Addition Of 'H Mrsmentioning
confidence: 78%
“…A 31P MRS study of neonatal dog brain documented similar changes (Young et al, 1985). A subsequent study of the same preparation found that seizure discharge produced by electroshock was followed by only slow return of PCr and Pi to control levels, a phenomenon attributed by the authors to low endogenous stores of high-energy phosphates or less developed pathways for their regeneration in the immature brain (Young et al, 1987~).…”
Section: Animal Studiesmentioning
confidence: 79%
“…A hipótese atualmente mais discutida para explicar lesão cerebral pós-crise prolongada é a excitotoxidade, em que a liberação excessiva de aminoáci-dos excitatórios (glutamato, aspartato, quisqualato e ácido caínico), estimulando seus receptores pós-sinápticos, determinam alterações iônicas que resultam em acúmulo de cálcio intracelular 16 . Estudos utilizando espectroscopia por ressonância nuclear magnética sugerem que as crises neonatais não determinam alterações metabólicas e/ou hipoperfusão cerebral, a menos que ocorra hipoxemia significativa ou lactoacidose extrema 17 . Trabalhos experimentais reforçam estas observações clínicas, demonstrando não existirem evidências de que crises breves produzam lesão cerebral no animal imaturo 18,19 , exceto se o mesmo já possuir seu SNC previamente exposto a outros insultos 20 .…”
Section: Tabela 1 -Classificação Clínica De Crises Convulsivas Neonataisunclassified